Learning English Across Borders: Nepali Students’ Experiences in Nepal and Australia - Hari Prasad Tiwari (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
The students’ experiences, perceptions, and outcomes of learning English may be affected by the different methods and practices of English Language Teaching (ELT). Methods and strategies used in ELT may differ from one country to another due to various factors. This qualitative study employed an interpretive framework and narrative inquiry approach to explore the way Nepali students learned English in Nepali and Australian contexts. The participants involved five Nepali students who studied an advanced-level English for Academic Preparation (EAP) course at Melbourne City College Australia (MCCA). The researcher employed snowball sampling to select the subjects. The technique used in data collection was a semi-structured interview. All the interviews were audio recorded and transcribed verbatim. The data was coded and categorized using thematic analysis to find common themes and patterns. The findings revealed significant differences in the teaching methods, vocabulary instruction, feedback practices, and technology use. The study emphasized the importance of using pedagogical strategies that foster communication skills, contextual vocabulary learning, constructive feedback, and technology integration for effective ELT.